1996
DOI: 10.1021/bi951503y
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Glycoprotein Ib and the Seven Transmembrane Domain Receptor to Increases in Platelet Cytoplasmic [Ca2+] Induced by α-Thrombin

Abstract: The individual contributions of glycoprotein Ib (GPIb) and the seven transmembrane domain receptor (STDR) to increases in platelet [Ca2+]i induced by alpha-thrombin or the tethered ligand peptide (TLP; SFLLRNPNDKYEPF) have been determined in control platelets, in platelets where the thrombin binding site on GPIb was blocked with the monoclonal antibodies TM60 and LJ-Ib10, in platelets where access of thrombin to the STDR was blocked by polyclonal antipeptide antibodies, and in Bernard-Soulier platelets which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 43 publications
6
68
2
Order By: Relevance
“…Thrombin binds to PAR1 and cleaves the peptide bond between Arg 41 and Ser 42 (10). The peptide LLRNPNDKYEPF represents amino acids 44 -55 of PAR1, and an antibody to this peptide, anti-STDR, inhibits thrombin binding to PAR1 (11) Anti-STDR failed to block factor XII binding (Fig. 5).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thrombin binds to PAR1 and cleaves the peptide bond between Arg 41 and Ser 42 (10). The peptide LLRNPNDKYEPF represents amino acids 44 -55 of PAR1, and an antibody to this peptide, anti-STDR, inhibits thrombin binding to PAR1 (11) Anti-STDR failed to block factor XII binding (Fig. 5).…”
Section: Discussionmentioning
confidence: 98%
“…Specific targeting of either receptor should modulate the effect of thrombin on platelets without inhibiting thrombin-induced proteolysis or the effects of other agonists for platelets including ADP, collagen, and thromboxane A2. Greco et al (11) have presented evidence that both GP Ib and PAR1 are required to ensure optimal rate and extent of platelet responses, such as an increase in intracellular Ca 2ϩ , at a range of thrombin concentrations of 0.3-10 nM. Recently a third human protein, PAR4 (12), has been shown to be involved in thrombin activation of platelets at high thrombin concentrations, e.g.…”
mentioning
confidence: 99%
“…Flow cytometry 36 confirmed the surface expression of a P 2X1 receptor(s) using both the anti-hP 2X1 antibody (described above) and an anti-rat P 2X1 antibody (kindly provided by Dr Julian Barden, University of Sydney, Australia) directed against an identical amino acid sequence in the human receptor. Both Dami cells and CMK 11-5 cells demonstrated binding of both antibodies (data not shown).…”
Section: Flow Cytometrymentioning
confidence: 95%
“…[6][7][8][9][10] GPIb-IX also binds thrombin and is important in thrombin-induced platelet activation. [11][12][13][14][15] The signaling mechanism of GPIb-IX-mediated integrin activation is not fully understood but may involve coordination of multiple signaling pathways. 9,[16][17][18][19] We recently have shown that ligand binding to GPIb-IX induces elevation of intracellular cGMP and activation of cGMP-dependent protein kinase (protein kinase G, PKG), 20 which leads to activation of extracellular signal-regulated kinase (ERK) and activation of ␣ IIb ␤ 3 .…”
Section: Introductionmentioning
confidence: 99%